2017
DOI: 10.4274/tjcd.82956
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Platelet-to-Lymphocyte Ratio in Predicting Liver Metastasis and Lymph Node Positivity of Colorectal Cancer Patients

Abstract: Amaç: Kolon kanserine bağlı mortalite azalsa da hala yüksektir. Kolonoskopinin artan kullanımı, cerrahi teknolojide ilerlemeler, kemoradyoterapi protokollerinin standardizasyonu metastatik olgularda sağkalımı arttırmıştır. Enflamasyon, birçok kanserin gelişiminde önemli rol oynar. Plateletlenfosit oranı (PLO) gibi birçok belirteç kanserde kötü prognoz ile ilişkilendirilmiştir. Çalışmamızda preoperatif bakılan PLO'nun kolon kanserli hastalarda karaciğer metastazını ve lenf nodu pozitifliğini öngörebilirliğini s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A small number of articles reported the threshold for the investigated inflammatory ratios on patients with colorectal cancer regarding metastasis as the outcome. Anuk and Yıldırım reported a cut-off value for PLR equal to 194.7 for liver metastasis (Se = 74.5.%, Sp = 72.7%) and of 163.95 (Se = 56.8%, Sp = 56.3%) for lymph node tumour cells invasion [62] on a sample of 152 patients. The thresholds for PLR reported in this study are higher than those reported by Anuk and Yıldırım [62], nonetheless the specificity is higher at the expense of sensitivity (Tables 2 and 6).…”
Section: Findings Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of articles reported the threshold for the investigated inflammatory ratios on patients with colorectal cancer regarding metastasis as the outcome. Anuk and Yıldırım reported a cut-off value for PLR equal to 194.7 for liver metastasis (Se = 74.5.%, Sp = 72.7%) and of 163.95 (Se = 56.8%, Sp = 56.3%) for lymph node tumour cells invasion [62] on a sample of 152 patients. The thresholds for PLR reported in this study are higher than those reported by Anuk and Yıldırım [62], nonetheless the specificity is higher at the expense of sensitivity (Tables 2 and 6).…”
Section: Findings Discussionmentioning
confidence: 99%
“…Anuk and Yıldırım reported a cut-off value for PLR equal to 194.7 for liver metastasis (Se = 74.5.%, Sp = 72.7%) and of 163.95 (Se = 56.8%, Sp = 56.3%) for lymph node tumour cells invasion [62] on a sample of 152 patients. The thresholds for PLR reported in this study are higher than those reported by Anuk and Yıldırım [62], nonetheless the specificity is higher at the expense of sensitivity (Tables 2 and 6). In our study we did not devided into the type of metastasis, but the differences in thresholds and Se(s) are important and could be possible explained by the characteristics of the target population.…”
Section: Findings Discussionmentioning
confidence: 99%